Production of charged monodisperse water droplets By electrical dispersion (MAUSAM, 1984)
Observations of an experiment for production of highly charged uniform water droplets by the electrical dispersion technique are described. It is observed that in dripping mode, the drop size decreases and frequency of drop production increases as the applied potential is increased. Minimum spraying potential is observed to be higher for capillaries of larger outer diameters. In spraying mode the voltage required to produce monodisperse streams of water droplets is very critical and a slight variation in it produces nonuniformity in drop sizes. At this critical voltage the dropsize is found to depend mainly on the flow fate. Measured values of specific charge on the droplets are compared to the theoretically calculated ones and found to be little more than half of the Rayleigh's limit of instability. The voltage required to produce a mist of very fine monodisperse particles is found to increase with the thickness of the capillary tube.